2011
DOI: 10.1038/eye.2011.109
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lytic C5b-9 induces functional changes in retinal pigment epithelial cells consistent with age-related macular degeneration

Abstract: Purpose There is evidence for complement dysfunction in age-related macular degeneration (AMD). Complement activation leads to formation of the membrane attack complex (MAC), known to assemble on retinal pigment epithelial (RPE) cells. Therefore, the effect of sub-lytic MAC on RPE cells was examined with regard to pro-inflammatory or pro-angiogenic mediators relevant in AMD. Methods For sub-lytic MAC induction, RPE cells were incubated with an antiserum to complement regulatory protein CD59, followed by normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 48 publications
(45 reference statements)
3
50
0
Order By: Relevance
“…Both appear to involve chronic inflammation of the RPE through sublethal deposition of the MAC (49). In Abca4 Ϫ/Ϫ mice and STGD1 patients, complement attack on RPE cells is stimulated by bisretinoid accumulation and subsequent oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Both appear to involve chronic inflammation of the RPE through sublethal deposition of the MAC (49). In Abca4 Ϫ/Ϫ mice and STGD1 patients, complement attack on RPE cells is stimulated by bisretinoid accumulation and subsequent oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins can deposit on the plasma membrane of RPE cells to create a sublytic complex that degrades RPE function without killing the cell (45,46). CD46 is expressed in the basolateral membranes of human RPE cells, where it is exposed to the choroidal circulation.…”
Section: Accumulation Of Bisretinoid Pigments In the Rpe Of Abca4mentioning
confidence: 99%
“…This molecule is the most important surface-bound negative regulator of complement activation on RPE cells [23]. In our previous study an enhanced cytokine production by RPE cells was found by a protocol using an antiserum targeting CD59 before the addition of human complement serum (HCS) [24]. …”
Section: Introductionmentioning
confidence: 99%